Epigenetics of paediatric acute myeloid leukaemia. (5th December 2019) - Jones, Luke; McCarthy, Peter; Bond, Jonathan
Summary: Comprehensive cataloguing of the acute myeloid leukaemia (AML) genome has revealed a high frequency of mutations and deletions in epigenetic factors that are frequently linked to treatment resistance and poor patient outcome. In this review, we discuss how the epigenetic mechanisms that underpin normal haematopoiesis are subverted in AML, and in particular how these processes are altered in childhood and adolescent leukaemias. We also provide a brief summary of the burgeoning field of epigenetic‐based therapies, and how AML treatment might be improved through provision of better conceptual frameworks for understanding the pleiotropic molecular effects of epigenetic disruption.